Fabrication and Characterization of Hierarchical Porous TiO2 Films - Li, Yanhua; Zeng, Dongming (Asian Journal of Chemistry, 2012)
Hierarchical porous TiO2 films with macroporous and mesoporous structures are prepared by drop-coating a mixed solution of polystyrene spheres and TiO2 colloid, followed by sintering to remove polystyrene spheres. XRD shows that crystal phase of TiO2 particles is major anatase structure with minor brookite structure. AFM displays that particle size distribution of porous TiO2 films ranges from 20-30 nm. SEM shows that TiO2 films prepared by drop-coating TiO2 colloid present mesoporous structure with a size of 8-50 nm. However, TiO2 films prepared by drop-coating the mixture containing polystyrene spheres and TiO2 colloid possess hierarchical porous structure with a mesoporous size of 8-50 nm and a macroporous size of about 600 nm. Besides, macropore ratios increase with increase of the ratio of polystyrene spheres to TiO2 colloid. UV-visible absorption spectra indicate that porous TiO2 films prepared at a polystyrene spheres/TiO2 colloid ratio 1, have the highest absorption intensity.